A General Dynamic Demographic Scheme and Its Application to Italy and the United States - Vianelli, Silvio (Econometrica, 1936)
1. In the past few years there has been a reawakened interest in studies oI1 the development of population, especially ill research for a general law regulating this development. However, the first steps were taken on ground still full of prejudices and old determinisms, so that the results obtained were really not too satisfactory. The formulation of too simple hypotheses and the excessive importance given to considerations and analogies of a pure biological character have led the greater part of those who are interested in the question to the creation of the scheme called the normal logistic. From the old scheme of Verhulst1 to the modern one of Pearl and Reed,2 Yule,3 Delevsky,4 and others, all sorts of attempts have been made to compel the various populations, y, to follow in time, t, the function,